Slay Your Day: Rahasia Feminine Hygiene Remaja - Irma, Irma; Sallo, Andi Kamal M (STIE Pelita Nusantara, 2024)
The socialization of feminine hygiene practices for Generation Z adolescent girls is a crucial step in improving their health and well-being. The